A Comparative Study Between the Climate Response Strategies and Thermal Comfort of a Traditional and Contemporary Houses in KRG: Erbil - Morad, Diler Haji; Ismail, Serbest Khalil (Kurdistan Journal of Applied Research, 2017)
The hot and dry climate conditions in Erbil city has a main effect on the energy consumption and thermal performance of the house. In the last decade, residential sector in Kurdistan region government has consumed about 50% of total energy consumption. The contemporary dwelling did not consider climate consideration therefore; there was difficulty in achieving or obtaining thermal comfort conditions, without using electrical or mechanical devices like air- conditioning. In contrast, traditional houses carefully and effectively designed with climate conditions. In the present study, in order to determine suitable architectural strategy that may be benefit in future housing designs, the climate response strategies and thermal comfort examined in both traditional and contemporary houses in Erbil city and evaluated in terms of building form, orientation, occupancy migration, plan arrangement, window, ventilation, shading, Vegetation, water bodies building materials and Urban Fabric. At the end of this study, a simplified evaluation and comparison between contemporary and traditional house are given.